The Effectiveness of Interactive Worksheets in Improving Student Learning Outcomes at SMAN Bandar Lampung - Faridatul Mutmainah; Urifatul Asmui; Yanuar Bimantara (JINEA: Journal of Innovation in Education and Learning, 2025)
Learning often faces challenges such as low student engagement and the lack of media that facilitates independent concept discovery. This study aims to analyze the effectiveness of interactive Student Worksheets (LKPD) in improving the learning outcomes of tenth-grade students at SMAN Bandar Lampung. The research employed a quasi-experimental method with a pretest-posttest control group design. The subjects consisted of two classes: the experimental class used interactive LKPD based on Discovery Learning, while the control class used conventional LKPD. Learning outcomes were measured using a validated multiple-choice test and analyzed with an independent t-test at a 5% significance level. The results indicated that the experimental class achieved significantly higher posttest scores than the control class (p < 0.05), with a high category gain score in the experimental class and a medium category in the control class. These findings demonstrate that interactive LKPD based on Discovery Learning is effective in enhancing student learning outcomes on the ecosystem topic. The application of interactive learning media aligned with active learning approaches is recommended to improve the quality of learning interactive.